Combined DNA methylation and gene expression profiling in gastrointestinal stromal tumors reveals hypomethylation of SPP1 as an independent prognostic factor. Issue 5 (1st August 2014) - Haller, Florian; Zhang, Jitao David; Moskalev, Evgeny A.; Braun, Alexander; Otto, Claudia; Geddert, Helene; Riazalhosseini, Yasser; Ward, Aoife; Balwierz, Aleksandra; Schaefer, Inga‐Marie; Cameron, Silke; Ghadimi, B. Michael; et al.
<x xml:space="preserve">Abstract</x> Gastrointestinal stromal tumors (GISTs) have distinct gene expression patterns according to localization, genotype and aggressiveness. DNA methylation at CpG dinucleotides is an important mechanism for regulation of gene expression. We performed targeted DNA methylation analysis of 1.505 CpG loci in 807 cancer‐related genes in a cohort of 76 GISTs, combined with genome‐wide mRNA expression analysis in 22 GISTs, to identify signatures associated with clinicopathological parameters and prognosis. Principal component analysis revealed distinct DNA methylation patterns associated with anatomical localization, genotype, mitotic counts and clinical follow‐up. Methylation of a single CpG dinucleotide in the non‐CpG island promoter of SPP1 was significantly correlated with shorter disease‐free survival. Hypomethylation of this CpG was an independent prognostic parameter in a multivariate analysis compared to anatomical localization, genotype, tumor size and mitotic counts in a cohort of 141 GISTs with clinical follow‐up. The epigenetic regulation of SPP1 was confirmed in vitro, and the functional impact of SPP1 protein on tumorigenesis‐related signaling pathways was demonstrated. In summary, SPP1 promoter methylation is a novel and independent prognostic parameter in GISTs, and might be helpful in estimating the aggressiveness of GISTs from the intermediate‐risk category.